Environmental, Social, and Economic Impacts of Transportation on Students and Parents in the State of Kuwait: A Qualitative Study in Light of the Sustainable Development Goals and Kuwait Vision 2035 (Architecture Image Studies, 2025)
This qualitative study aimed to explore the environmental, social, and economic impacts of transportation systems on students and their parents in the State of Kuwait, and to analyze the extent to which these impacts align with the Sustainable Development Goals and the "New Kuwait 2035" vision. The study adopted a case study approach and utilized semi-structured interviews as the primary data collection tool. A total of 15 participants from diverse social and professional backgrounds were selected to ensure a broad range of perspectives and experiences. The interviews focused on five main themes that correspond to the study’s research questions: the integration of environmental considerations in transportation planning; the evaluation of social impacts such as safety and school commuting; the economic burden of family transportation; participants’ perceptions of equity in the distribution of transportation services; and the level of awareness regarding the concept and objectives of sustainable transport. The findings revealed significant gaps in the integration between the transportation and education sectors, as well as a lack of geographic and social equity in the distribution of school transport services. Families, particularly in peripheral areas, bear a substantial economic burden. Furthermore, the study identified limited public and institutional awareness of sustainable transport and a lack of planning and assessment tools grounded in environmental and social justice principles.